Running Lean : iterate from plan A to a plan that works - Maurya, Ash (Lean series., 2012)
We live in an age of unparalleled opportunity for innovation. We're building more products than ever before, but most of them fail--not because we can't complete what we set out to build, but because we waste time, money, and effort building the wrong product. What we need is a systematic process for quickly vetting product ideas and raising our odds of success. That's the promise of Running Lean. In this inspiring book, Ash Maurya takes you through an exacting strategy for achieving a "product/market fit" for your fledgling venture, based on his own experience in building a wide array of product.- Resumé vydavatel